Hazard due to earthquake-induced rock falls: The use of remote sensing data and field mapping in the case of Skolis Mountain, NW Peloponnese - Litoseliti, A.; Koukouvelas, I.; Nikolakopoulos, K. (Bulletin of the Geological Society of Greece, 2014)
Inventory of pre-earthquake and earthquake triggered landslides is used to provide insight of the tectonic forcing in the development of the rock slopes of the Skolis Mountain, in the North Peloponnese. For the purposes of inventory of landslides we analyzed © Google Earth photographs based on drawing polygons and paths in order to create ‘Keyhole Markup Language’ or KML files. © Google Earth photographs analysis and surface mapping indicate that the Skolis Mountain is affected by long- term climatically and tectonically controlled rock falls and minor rock slides. The rock falls show a progressive inflation in surface area from 2007 to 2009. The post-earthquake surface area of the rock falls increased three times. In addition, there was a series of rock falls descending Skoli’s slopes by free fall, bouncing, or rolling causing damages in the Santomerion village and blocking significant part of the dirt roads around it. These boulders are clustered in three areas across the western bluff of the mountain.